Differences in Thawing Methods in Broiler Chicken Meat on Total Plate Count (TPC) of Bacteria - Putri, Noorlaily; Lutpiatina, Leka; Insana, Aima; Nurlailah, Nurlailah (Baiman Bauntung Batuah Center, 2024)
Total Plate Count (TPC) determines the number of microorganisms, both bacteria and fungi. Thawing is a step in thawing food that was previously stored frozen. This study aims to analyze the differences in the Total Plate Count of bacteria with variations in thawing methods in broiler chicken meat. Thawing methods commonly used include thawing at room temperature, soaking in water, and leaving it in the refrigerator (chiller). The type of research is experimental design with a posttest-only control design. Repetition was carried out five times for each control group KN (negative control) and test groups R0 (fresh chicken), R1 (frozen chicken), R2 (chicken thawed at room temperature), R3 (chicken soaked in water) and R4 (chicken thawed in the chiller) then the number of bacteria that grew was calculated. The average number of R0 colony results ranged from 4.1 x 103 CFU/g, R1 8.6 x 102 CFU/g, R2 1.6 x 104 CFU/g, R3 8.9 x 103 CFU/g and R4 1.2 x 103 CFU/g. The Kruskall-Wallis test results showed an Asymp sig value of 0.000 (<0.05); it can be concluded that there are differences in TPC in broiler chicken meat with variations in thawing methods that are thawed at room temperature, soaked in water and thawing in the chiller. It is recommended to thaw frozen chicken meat using the method of leaving it in the refrigerator because it has the lowest number of germs and can inhibit the growth of germs.